PERCEPTION OF THE MILLENNIAL GENERATION TOWARDS THE USE OF TONTEMBOAN LANGUAGE (the study conducted at Pinamorongan village) - Pinatik, Riedel; Samola, Nurmin; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aims at revealing the perception of the millennial generation in Pinamorongan village towards the use of Tontemboan language. This type of research is descriptive research with a qualitative approach. Data collection techniques in this research used a questionnaire. For data analysis technique used in this research is from Miles and Huberman (1984) in Sugiyono (2015: 330), namely: Data Reduction, Data Display, Conclusion / Verification.Based on the results of the research that has been done, it can be seen that the people in Pinamorongan village, especially the millennial generation, rarely use the Tontemboan language because of the times and it has not been preserved until now. therefore there must be awareness from all people, both young and old, to be able to love culture and in particular to continue to preserve the Tontemboan language in Pinamorongan village